2011
DOI: 10.1021/ie202617h
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of SO2 and NO from Flue Gas Using Multicomposite Active Absorbent

Abstract: A multicomposite active absorbent was prepared using the liquid-phase complex of NaClO2 and NaClO as well as solid-phase slake lime to simultaneous desulfurization and denitrification at a flue gas circulating fluidized bed (CFB). The effects of influencing factors on the removal efficiencies of SO2 and NO were investigated. Removal efficiencies of 96.5% for SO2 and 73.5% for NO were obtained, respectively, under the optimal experimental conditions. The characterization of the spent absorbent was carried out b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…(12)) was also contributed to the oxidation reactions [15,23,26,28,35,44]. Moreover, ClO 2 could generate Cl Á and Cl 2 via the reactions of 15 to 17, which had been demonstrated previously [15,28,44].…”
Section: Products Characterization and Reaction Mechanismmentioning
confidence: 58%
See 2 more Smart Citations
“…(12)) was also contributed to the oxidation reactions [15,23,26,28,35,44]. Moreover, ClO 2 could generate Cl Á and Cl 2 via the reactions of 15 to 17, which had been demonstrated previously [15,28,44].…”
Section: Products Characterization and Reaction Mechanismmentioning
confidence: 58%
“…For a coal-fired power plant, the actual flue gas consists chiefly of N 2 , CO 2 , O 2 , SO 2 , NO x etc., in which the concentrations of CO 2 and O 2 are generally 10-15% and 5-6%, respectively, and those of SO 2 and NO x will change with coal species and combustion conditions of the boiler [35]. In order to investigate the interactions of the coexistence gases in coal-fired flue gas with SO 2 , NO and Hg 0 , the simultaneous removal experiments with various concentrations of O 2 , CO 2 , NO and SO 2 were carried out.…”
Section: Effects Of Coexistence Gases In Simulated Flue Gas On the Simentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results revealed that the elevated pH ranging from 4.5 to 7.0 was unfavorable for the removal of NO and Hg 0 , which might be a consequence of the followed reasons. On the one hand, it had been known that the acidic environment was preferable for the H 2 O 2 -induced oxidation reaction [18], whereas the increasing pH in the range of 4.5-7.0 would accelerate the decomposition of H 2 O 2 due to the excessive HO 2 − generations (Eq.…”
Section: Effect Of the Co Ph On The Simultaneous Removalmentioning
confidence: 99%
“…The SO 2 and NO concentrations in actual flue gas always change with various operation conditions [18]. Importantly, they have great influences on the Hg 0 removal [19][20][21][22][23][24], so a series of experiments with different concentrations of NO and SO 2 were carried out.…”
Section: Effects Of Coexistence Gases On the Simultaneous Removalmentioning
confidence: 99%